O ensino médio integrado e a construção dos projetos de vida da juventude egressa do IFAM Campus Presidente Figueiredo - Silva, Juliana Pinheiro da (2022)
The Integrated Secondary Teaching offered by the Federal Institute of Education, Science and Technology of Amazonas (IFAM), in the municipality of Presidente Figueiredo - AM, began in 2010. In 2020 the institution accounted for approximately 450 young graduates. Despite this expressiveness, when we searched for results on the eduCAPES platforms and the Brazilian Digital Library of Teses and Dissertations (BDTD), it was not possible to find research referring to graduates of that institution, or considering the perspective of those young people about their formative trajectory. Therefore, the present work identified the relationship between Integrated Secondary Teaching (IST) and the construction of life projects of the youth who graduated from IFAM, Campus Presidente Figueiredo, as well as indicated a script of items dedicated to the optimization of the institutional page of the IFAM as a monitoring mechanism for graduates of EPTNM courses. Therefore, this research was based on the contributions of Juarez Dayrell, about the youth category; Leão, Dayrell and Reis, in their discussion on the life project category; Moura, Saviani, Silva and Ramos, in their discussions about the Integrated Secondary Teaching and the EPT, in addition to the contributions of Bauer and Jovchelovitch, in view of the perspective of the Narrative Interview. The methodology used consisted of a qualitative approach of a basic nature. Data were collected through field research from the collection of narrative interviews of 21 graduates of the Integrated Technical Course in Electrotechnics at IFAM Campus Presidente Figueiredo, which were analyzed using the technique of thematic analysis, according to Bardin's perspective. Through this research, which is linked to the Organization and Memories of Pedagogical Spaces in Professional and Technological Education Research Line, in Macroproject 4 – Histories and Memories in the context of EPT - of the Professional Master's Program in Professional and Technological Education (ProfEPT/IFAM, Manaus Centro) –, it was found that the construction of life projects of youths is based on their historical context; of a given concrete material reality. In this sense, IFAM has contributed to fostering the construction of life projects of its students, helping them to broaden their horizons and the possibilities of carrying out these projects. In addition, the research also indicated the need for the institution to seek tools such as an institutional website for its graduates, in order to approach and maintain a bond with its former students, as a form of self assessment and a mechanism to continue contributing to projects. academic and professional life of graduates.